Determinant Factors for the Formation of Entrepreneurial Ability and Character in Private Teacher Training Colleges - Dewi Amaliah Nafiati; Sukirno; Novie Kurniasih Kamaruddin; Eni Dwi Rusjayanti (Dinamika Pendidikan, 2024)
This research aims to examine the relationship between ability and effort, intellectual skills, emotional skills, spiritual skills, digital skills and students' entrepreneurial character and abilities. The quantitative method was obtained through an online survey involving 200 students from Private IKIP in Central Java. Data were analyzed using Structural Equation Modeling (SEM), because it is able to test complex relationships between latent variables and indicators simultaneously and provide accurate estimates of the structural and measurement models. The research results show that ability (AE) has a significant relationship of 1.15%, while emotional skills (ES) make a small contribution of 0.13% to entrepreneurial character (later_var1). Intellectual skills (CG) have a strong influence of 0.04%, Digital Skills (DS) have a strong influence of 0.21%, and spiritual skills (SS) have a strong influence of 0.91% on entrepreneurial ability (laten_var2). However, no significant direct relationship was found (0%) between entrepreneurial character (laten_var1) and entrepreneurial ability (laten_var2). These findings show that ability and effort, intellectual skills, emotional skills, spiritual skills, digital skills can shape character and entrepreneurial abilities. This study identifies limitations of the model and sample, and recommends moderating factors in future research.